DECISION SUPPORT SYSTEMS FOR ASESSING THE QUALITY OF TEACHING MATERIALS IN E-LEARNING-BASED LEARNING AND DESIGNING TEACHING MATERIALS MANAGEMENT USING LEARNING STYLE AND HTSC (HIGH TECHNOLOGY SPIRITUAL COMMUNICATION) METHODS - melva sari panjaitan (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2021)
In the lecture system, it is necessary to have e-Learning based learning in the form of video which includes learning elements that are in accordance with predetermined conditions. High Technology Spiritual Communications is a communication system that was first introduced by the late Harvard University graduate, Indrawan Hatoguan Siregar, Ph.D, who is also a permanent lecturer at Panca Budi Development University. This research discusses the use of the internet and LMS (Learning Management System) as the communication media and the application of HTSC (Hight Technology Spiritual Communications). The advantage in this application is that students can watch videos of teaching materials anytime, anywhere without having to spend special time reading, even students can listen to them while working. The result of this research is that it can divide the learning group into 3 groups, average value, weighting criteria, have a decision matrix, and get the most ideal ranking results.